Clinical and electroencephalographic correlations in patients with cerebral ischemic hemispheric stroke in early recovery period of disease - S. O. Medvedkova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim is to investigate the state of bioelectric activity of the brain in comparison with clinical neurological data in patients with cerebral ischemic hemispheric stroke (CIHS) in the early recovery period of the disease.